In Vitro Evaluation of Colistin Conjugated with Chitosan-Capped Gold Nanoparticles as a Possible Formulation Applied in a Metered-Dose Inhaler - Narumon Changsan; Apichart Atipairin; Poowadon Muenraya; Rutthapol Sritharadol; Teerapol Srichana; Neelam Balekar; Somchai Sawatdee (MDPI AG, 2024)
Inhaled colistin is used to treat pneumonia and respiratory infections through nebulization or dry powder inhalers. Nevertheless, the development of a metered-dose inhaler (MDI) for colistin, which could enhance patient convenience and treatment efficacy, has not yet been developed. Colistin is known for its ability to induce cellular toxicity. Gold nanoparticles (AuNPs) can potentially mitigate colistin toxicity. Therefore, this study aimed to evaluate the antimicrobial effectiveness of colistin conjugated with chitosan-capped gold nanoparticles (Col-CS-AuNPs) and their potential formulation for use with MDIs to deliver the aerosol directly to the deep lung. Fourier-transform infrared spectroscopy, nuclear magnetic resonance, and elemental analysis were used to characterize the synthesized Col-CS-AuNPs. Drug release profiles fitted with the most suitable release kinetic model were evaluated. An MDI formulation containing 100 µg of colistin per puff was prepared. The aerosol properties used to determine the MDI performance included the fine particle fraction, mass median aerodynamic diameter, and geometric standard deviation, which were evaluated using the Andersen Cascade Impactor. The delivered dose uniformity was also determined. The antimicrobial efficacy of the Col-CS-AuNP formulation in the MDI was assessed. The chitosan-capped gold nanoparticles (CS-AuNPs) and Col-CS-AuNPs had particle sizes of 44.34 ± 1.02 and 174.50 ± 4.46 nm, respectively. CS-AuNPs effectively entrapped 76.4% of colistin. Col-CS-AuNPs exhibited an initial burst release of up to 60% colistin within the first 6 h. The release mechanism was accurately described by the Korsmeyer-Peppas model, with an R2 > 0.95. The aerosol properties of the Col-CS-AuNP formulation in the MDI revealed a high fine particle fraction of 61.08%, mass median aerodynamic diameter of 2.34 µm, and geometric standard deviation of 0.21, with a delivered dose uniformity within 75-125% of the labeled claim. The Col-CS-AuNP MDI formulation completely killed Escherichia coli at 5× and 10× minimum inhibitory concentrations after 6 and 12 h of incubation, respectively. The toxicity of CS-AuNP and Col-CS-AuNP MDI formulations in upper and lower respiratory tract cell lines was lower than that of free colistin. The stability of the Col-CS-AuNP MDI formulation was maintained for at least 3 months. The Col-CS-AuNP MDI formulation effectively eradicated bacteria over a 12-h period, showing promise for advancing lung infection treatments.